160 Triage of cardiac imaging testing did not impact patient outcomes in a large cardiac network during the covid-19 pandemic. (6th June 2022) - Joshi, Abhishek; Cashin, Shane; Laskar, Nabila; Ahluwalia, Nikhil; Cheasty, Emma; Menezes, Leon; Bhattacharyya, Sanjeev; Moon, James; Woldman, Simon; Lloyd, Guy
Abstract : Background: The first wave of the COVID-19 pandemic required rapid reconfiguration and reallocation of resources. We triaged all cardiac imaging requests from our referral network serving 2.5 million people, to our tertiary centre, performing only clinically urgent studies and cancelling non-urgent studies. Requesters received notification of cancellation in the same format as test reports and were encouraged to repeat their request when pandemic conditions had improved. The impact of this cancellation on patient outcomes is assessed. Methods: Retrospective analysis of routinely collected clinical and administrative data from the institutional data warehouse determined patient outcomes for those with cancelled and performed stress echocardiography, nuclear stress perfusion studies, cardiac CT angiography and cardiac MRI. Mortality data was drawn from the NHS spine. Data analysis was performed using R. Results: 1600 cardiac studies for 1592 patients were cancelled in April 2020, and 2234 cardiac studies were performed for 2184 patients between April and July 2020, representing high-risk outpatient requests. 41 patients who had cancelled scans died, and 105 patients with performed scans died (table 1). Of cancelled scans, 787 patients had a subsequent scan in some modality, of which 701 were the same modality as the original test. 761 patients had no repeat outpatient testing until October 2021. Mortality was higher in patients for whom scans were performed (log-rank p = 0.03, figure 1A). Non-elective admissions were higher in patients who had scans performed (4% in cancelled vs. 8% performed after 574 days of follow-up, log-rank p <0.001 figure 1B). Over the course of the pandemic, our wait-times for cardiac testing did not exceed the national standard of 16 weeks.Limitations: Data was not collected prospectively, due to the level of emergency; cancellation data may not be complete. All cause mortality under pandemic conditions cannot be extrapolated to non-pandemic situations. Conclusion: Our approach to diagnostic testing in cardiology during the first wave of the COVID-19 pandemic accurately identified and tested high-risk patients without causing harm to those at lower risk, demonstrated by higher admission rates in patients in whom tests were performed, and the absence of an adverse impact on mortality. 49% of patients underwent subsequent cardiac testing after a cancelled test. We maintained low waiting times throughout the pandemic. Conflict of Interest: None